Prognosis of urgent initiation of peritoneal dialysis: a systematic review and meta-analysis - Ji He; BaoQiao Wu; Yue Zhang; Limiao Dai; Juan Ji; Yueming Liu; Qiang He (Renal Failure)
Objectives Currently, there is no consensus on the optimal timing for the initiation of peritoneal dialysis (PD) after catheter placement.Design Systematic review and meta-analysis.Exact date of data collection From inception till July 31, 2023.Main outcome measures To assess the outcomes and safety of unplanned PD initiation (<14/7 days after catheter insertion) in cohort studies.Results Fifteen studies involving 3054 participants were included. (1) The risk of unplanned initiation of leakage and Obstruction was no difference in both the break-in period (BI) <14 and BI < 7 groups. (2) Catheter displacement was more likely to occur in the emergency initiation group with BI < 7. (3) No significant differences were observed between the two groups regarding infectious complications. (4) There was no difference in transition to HD between patients with BI < 7 and BI < 14 d.Conclusion Infectious complications of unplanned initiation of peritoneal dialysis did not differ from planned initiation. Emergency initiation in the BI < 7 group had higher catheter displacement, but heterogeneity was higher. There were no differences in leakage or obstruction in either group. Catheter survival was the same for emergency initiation of peritoneal dialysis compared with planned initiation of peritoneal dialysis and did not increase the risk of conversion to hemodialysis.Registration This meta-analysis was registered on PROSPERO (https://www.crd.york.ac.uk/PROSPERO/, number: CRD42023431369)